English for Engineering at Defence Industry: A Language Metamorphosis? - Sultan Bagus Firmansyah (ETNOLINGUAL, 2021)
Innumerable flock of engineers does not conceive English language adeptly. This research scrutinizes linguistic disciplinarian as regards English for Engineering. Numerous samples have been mustered from PT. PAL Indonesia (Persero), the >35-year state-owned warship-building industry in Surabaya. They, the respondents, are in dilemma and hardship since General English (GE) poles apart from Technical English (TE). Exploratory Factor Analysis or EFA method transfigures the ‘English subject’ on to focal point, then; so does it reorients these clusters of English for Engineering as pioneer of:  (i). Translations, (ii). Supply Chain, (iii). Operation Manual Documents, (iv). Standard Operation Procedures, and (v). Object-oriented Analysis and Design/ OOAD. Foregoing multivariate language’s scope in English intermittently mystifies the engineer whether the grammar, structure, meaning, or the principle is common or not; a specific-based linguistic (English for Engineering) can expedite both technicians’ advance English learning furtherance and broaden the significance of English for Specific Purpose (ESP), later on.